Novel Vesicular System: An Overview - Seema M. Jadhav, Pournima Morey, Mrs. Manisha Karpe, Vilasrao Kadam (Journal of Applied Pharmaceutical Science)
Novel drug delivery attempts to either sustain drug action at a predetermined rate, or by maintaining a relatively constant, effective drug level in the body with concomitant minimization of undesirable side effects. The vesicular systems are highly ordered assemblies of one or several concentric lipid bilayer formed, when certain amphiphillic building blocks are confronted with water. The vesicular system such as liposomes, niosomes, sphingosomes, ethosomes, transferosomes and pharmacosomes are used to improve the therapeutic index of both existing and new drug molecules by encapsulating an active medicament inside vesicular structure in one such system. It prolongs the existence of the drug in systemic circulation and finally reduces the toxicity. Such different systems are widely used in gene delivery, tumor targeting, oral formulations, in stability and permeability problems of drugs. Now a days vesicle as a carrier system have become the vehicle of choice in drug delivery and lipid vesicles were found to be of value in immunology, membrane biology and diagnostic technique and most recently in genetic engineering.
Keywords: Vesicular system, controlled drug delivery, stability, applications.